Mature green tea leaves derived CDs as both reducing agent and stabilizer for synthesis of CD-AgNPs composite for Hg(II) ions detection - Swagata Patra; Animes K. Golder; Ramagopal V.S. Uppaluri (Next Nanotechnology, 2025)
A stable CD-AgNPs composite system has been synthesized with the carbon dots (CDs) that were synthesized from mature green tea leaves as a reducing and stabilizing agent. Accordingly, ambient temperature synthesis at the optimized process condition of 0.5 mL CDs solution, 10 mL of 5 mM silver nitrate (AgNO3) and 2 h reaction time were analysed to be the optimal process condition for the synthesis of highly sensitive and selective monodispersed CD-AgNPs and for Hg(II) sensing application. The synthesized CD-AgNPs were characterized with UV-Visible spectroscopy (426 nm), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and Field Emission Transmission Electron Microscopy (FETEM). The contacting of Hg(II) solution and the composite nanosystem at the 4 pH ascertained a color alteration from the reddish brown hue to the colorless state. Also, the color transition corroborated with the blue shift of localized surface plasmon resonance (LSPR) band and reduced absorbance of the CD-AgNPs composite. Integrating the finer findings of the XRD, FETEM and XPS analyses, the pertinent mechanism has been hypothesized in terms of the silver-mercury amalgam formation through the redox reaction between the CD-AgNPs composite system and Hg(II) system. In the deployed Hg(II) concentration range of 0.1–10 mg/L, the absorbance of the system altered as a linear model with good fitness. Thereby, the lowest LOD value of 0.009 mg/L was achieved. In summary, a highly sensitive system for Hg(II) detection has been confirmed and the interference effect has been insignificant with respect to other metal ions.